The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1027/0227-5910.29.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Suicidal Behavior and Attitudes Toward Suicide and Suicide Prevention Among Psychology Students in Ghana, Uganda, and Norway

Abstract: Self-reported suicidal behavior and attitudes toward suicide in psychology students are reported and compared in Ghana, Uganda, and Norway. Small differences only were found in own suicidal behavior. However, experience of suicidal behavior in the surroundings was more common in Uganda than in Ghana and Norway. Although differences were found between the three countries in attitudes toward suicide, which emphasizes the need for culture-sensitive research and prevention, many of the differences were not as big … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
61
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 32 publications
8
61
0
6
Order By: Relevance
“…Similar to our study, most studies from other countries find more accepting attitudes about suicide among those with more education (Salander Renberg & Jacobsson, 2003; Singh, Williams, & Ryther, 1986) so this appears to be a robust relationship cross-nationally. The higher acceptability of suicide among females found in our study is also found in some, but not all, studies from other countries (Agnew, 1998; Beautrais, Horwood, & Fergusson, 2004; Hjelmeland et al, 2008; Joe, Romer, & Jamieson, 2007; Kocmur & Dernovšek, 2003; Parker, Cantrell, & Demi, 1997; Salander Renberg & Jacobsson, 2003; Zemaitiene & Zaborskis, 2005); the finding in China could be related to the relatively high rate of suicide in Chinese females compared to that in other countries (WHO, 2002). Controversy remains about the relationship of age to attitudes about the acceptability of suicide (Salander Renberg et al, 2008; Salander Renberg & Jacobsson, 2003; Segal, Mincic, Coolidge, & O’Riley, 2004); the decreasing acceptability of suicide as individuals age (after adjusting for educational level) found in our study may be a reflection of an underlying culturally conditioned conservatism that results in increasing intolerance to all forms of social deviance (including suicidal behavior) as one ages.…”
Section: Discussionsupporting
confidence: 85%
“…Similar to our study, most studies from other countries find more accepting attitudes about suicide among those with more education (Salander Renberg & Jacobsson, 2003; Singh, Williams, & Ryther, 1986) so this appears to be a robust relationship cross-nationally. The higher acceptability of suicide among females found in our study is also found in some, but not all, studies from other countries (Agnew, 1998; Beautrais, Horwood, & Fergusson, 2004; Hjelmeland et al, 2008; Joe, Romer, & Jamieson, 2007; Kocmur & Dernovšek, 2003; Parker, Cantrell, & Demi, 1997; Salander Renberg & Jacobsson, 2003; Zemaitiene & Zaborskis, 2005); the finding in China could be related to the relatively high rate of suicide in Chinese females compared to that in other countries (WHO, 2002). Controversy remains about the relationship of age to attitudes about the acceptability of suicide (Salander Renberg et al, 2008; Salander Renberg & Jacobsson, 2003; Segal, Mincic, Coolidge, & O’Riley, 2004); the decreasing acceptability of suicide as individuals age (after adjusting for educational level) found in our study may be a reflection of an underlying culturally conditioned conservatism that results in increasing intolerance to all forms of social deviance (including suicidal behavior) as one ages.…”
Section: Discussionsupporting
confidence: 85%
“…The items no 41-43 were not included for the present study as these items were difficult to assess in Indian context where open discussion about suicide is regarded as taboo. Further, earlier research also supports the inclusion of these items in the present study (Arnautovska 2010;Hjelmeland et al 2008;Norheim et al 2013). However these studies have done their own factor analysis.…”
Section: Data Collection Instrumentssupporting
confidence: 67%
“…Although official national statistics on suicide are not available, crude estimates from some studies do indicate that the act is a growing public health problem in Ghana (Hjelmeland et al, 2008;Adinkrah, 2012). Progress has been made in suicide research in Ghana, especially in the area of attitudes toward the act and suicidal persons.…”
mentioning
confidence: 96%